Effect of passive smoking on haematological parameters in children - حربة, محمود; عبد المنعم غانم; فاطمة حلاج (Latakia University Journal -Medical Sciences Series, 2024)
Background: Passive smoking (PS) exposure is a major risk for children’s health, passive smoking contains more than 4000 chemical compounds, and which exposure or inhalation of these compounds leads to pathological changes on the haematological parameters, and these alterations might be associated with a greater risk for developing many diseases. Objective: The purpose of this study was to assess the effects of exposure to passive smoking on haematological parameters in children. Materials and Methods: An observational study (case study and reference) was conducted for the period one year (October 2022–October 2023) at Tishreen University Hospital in Lattakia-Syria. The study included two groups of children aged between (8-12) years and were compared: group I consisted of 66 children who had a history of exposure to passive smoking by their parents inside the house, whereas group II consisted of 58 children without a history of exposure to passive smoking. Complete blood count (CBC) and Lipid profile were performed and comparison values between two groups. Results: group with Chronic exposure to passive smoking had a significant increase (p=0,042) in hemoglobin, white blood cells (p<0,001), Cholesterol (p=0,04), Low-density lipoprotein (LDL) (p=0,05), and a significant decrease in High-density lipoprotein (HDL) (p=0,04) in comparison with non-exposure group. All other measured parameters did not differ significantly. We found an important relationship between exposure to passive smoking and pathological changes in the values of some blood parameters WBC>10,5 (×10e⁹/L) (ORs=3,3), HDL<45(mg/dL) (ORs=2,6). Conclusion: In conclusion, our study showed that children with exposure to passive smoking has adverse effects on haematological parameters (e.g., hemoglobin, white blood cells count, low density lipoprotein(LDL), High density lipoprotein(HDL) , Cholesterol ) and these alterations might be associated with a greater risk for developing atherosclerosis, chronic obstructive pulmonary disease and/or cardiovascular diseases at an early age.